Webb–Dattani Syndrome: Report of a Saudi Arabian Family with a Novel Homozygous Mutation in the ARNT2 Gene - Al-Sannaa, Nouriya Abbas; Pepler, Alexander; Al-Abdulwahed, Hind Y.; Al-Majed, Sami I.; Abdi, Rifat F.; Menzel, Moritz; Biskup, Saskia (Journal of Pediatric Neurology, 2019)
Webb–Dattani syndrome (WEDAS) is an autosomal recessive disorder caused by mutation in the ARNT2 gene characterized by frontotemporal hypoplasia, globally delayed development, and pituitary and hypothalamic insufficiency. The condition is reported to be associated with consanguinity and with Saudi Arabian ancestry. Here we describe a family of three affected siblings born to healthy second cousin parents of Saudi Arabian ancestry. The children presented at 3 months of age with congenital central hypotonia and hypoventilation, central diabetes insipidus, multiple pituitary hormone deficiency, severe developmental delay, acquired microcephaly, cortical blindness with normal retinal examination, seizures, and gastroesophageal reflux. Whole exome sequencing detected a homozygous unclear variant (c.378C>T; p.G126G) in the ARNT2 gene in both the affected twins. According to splice prediction programs, this variant results in the creation of a cryptic donor splice site, possibly leading to a loss of function. These data support the role of the detected mutation in the ARNT2 gene in causing the described phenotype.
Keywords: WEDAS; Webb–Dattani; ARNT2